CAPITAL MARKET INTEGRATION OF ASEAN-5 COUNTRIES : AN EMPIRICAL ANALYSIS - Tom Jacob; Rincy Raphael; M.V. Stebiya (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2021)
The financial integration of South East Asian markets has been an important research topic. Due to the recent global developments in financial markets, the behaviours of these emerging markets are gaining much interest. This research paper empirically analyzes stock market integration of international portfolio diversification across the South East Asian countries, namely Indonesia, Malaysia, Philippines, Singapore and Thailand. The Augmented Dickey-Fuller unit root test has been used to verify the static properties of the market return of ASEAN countries. An analysis of the co-integration among these countries' market return has been done using the Johansen Co-integration Approach. The co-movements between the ASEAN economies were analyzed through the Granger Causality test. The results of the Granger causality tests indicate the interdependence between ASEAN-5 market returns. This suggests a co-movement among ASEAN capital markets, but not all of these ASEAN capital markets were fully integrated. This study also found that the Malaysia Stock Exchange, the Stock Exchange of Thailand, the Singapore Stock Exchange and the Philippines Stock Exchange were fully integrated, but Indonesia Stock Exchange was not. Essentially, this study provides insight for policymakers, portfolio managers, domestic and international investors, risk analysts, and financial researchers to diversify their investment portfolios by combining assets from each ASEAN-5 country.